2023
DOI: 10.5551/jat.63383
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm of Subspecies of Low-Density Lipoprotein-Cholesterol and High-Density Lipoprotein-Cholesterol in Healthy Subjects and Patients with Type 2 Diabetes

Abstract: Aims:We established automated assay kits for quantifying small dense low-density lipoprotein (sdLDL)cholesterol (C), LDL-triglyceride (TG), and high-density lipoprotein (HDL)3-C, and apolipoprotein (apo)E-rich HDL-C, and these have been recognized as sensitive biomarkers for predicting coronary artery disease. We investigated the circadian rhythms of these novel lipids to determine if fasting is required to determine basal levels. Methods: Forty-eight inpatients with type 2 diabetes and 19 healthy volunteers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It is well accepted that LDL-C has no significant circadian rhythm, which suggests that sdLDL-C does not change during the day. In fact, we recently reported that direct sdLDL-C concentrations do not change significantly in a day even in the presence of postprandial hypertriglyceridemia 22) . Consistent with our previous results 22,23) , the present study confirmed that the values of direct sdLDL-C were similar in fasting and nonfasting plasmas.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is well accepted that LDL-C has no significant circadian rhythm, which suggests that sdLDL-C does not change during the day. In fact, we recently reported that direct sdLDL-C concentrations do not change significantly in a day even in the presence of postprandial hypertriglyceridemia 22) . Consistent with our previous results 22,23) , the present study confirmed that the values of direct sdLDL-C were similar in fasting and nonfasting plasmas.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, we recently reported that direct sdLDL-C concentrations do not change significantly in a day even in the presence of postprandial hypertriglyceridemia 22) . Consistent with our previous results 22,23) , the present study confirmed that the values of direct sdLDL-C were similar in fasting and nonfasting plasmas. Therefore, fasting is not necessary as long as sdLDL-C is measured using the direct method.…”
Section: Discussionmentioning
confidence: 96%
“…It can be used to measure various samples on an automated analyzer. In this issue, Hayashi et al clearly showed that small dense LDL-C concentration does not exhibit significant within-day variation in both controls and patients with diabetes 5) . Therefore, nonfasting small dense LDL-C concentration can be considered for fasting.…”
Section: See Article Vol 30: 3-14mentioning
confidence: 95%